Architectural Science in al-Ghazali's Classification of Knowledge - Achmad Khudori Soleh; Humaida Ghevira Syavia Camila (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2026)
Most people believe architecture is not religiously significant, so only a few people study architecture. This assessment does not align with al-Ghazali's teachings, which state that architecture is a science society needs. This research aims to analyze architectural science in al-Ghazali's classification of knowledge. The research uses a descriptive analysis method with the Ihya Ulūm al-Dĩn (Revival of Religious Science) as the primary source. The research results show that (1) al-Ghazali classified knowledge into three groups, namely classification based on sources, methods, and laws of searching for it. (2) Based on the law of mastering it, al-Ghazali divided knowledge into five laws: individual obligation, social obligation, primary, permissible, and reprehensible. (3) In the context of al-Ghazali's classification of science, architecture is included in the category of religiously significant science, and seeking it is subject to a collective obligation (farḍ kifayah). The results of this research significantly contribute to the development of architectural science (1), providing a religious basis for its importance. (2) provide practical guidance so the architectural profession can draw closer to God.